ANALISIS KESULITAN MEMBACA PERMULAAN PADA SISWA KELAS I DI SDN DEMANGAN YOGYAKARTA - Pridasari, Fifin; Anafiah, Siti (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2020)
The purpose of the research to describe the types of difficulties in reading the beginning, the causes of difficulty reading the beginning, and the efforts of the teacher in the face of difficulty reading beginning in Grade 1 students at SDN Demangan Yogyakarta. This type of research is qualitative descriptive research, with data collection using interviews, observations, and documentation. The results show that there are types of difficulties in reading the beginning of students, namely the lack of student recall, difficulty spelling when the consonant is in the middle, difficulty seeing long distances, mistakes in changing letters, not yet Punctuation and difficulties in letter recognition. Factors for the cause of difficulty reading early physiological, intellectual, psychological, and solutions and efforts that have been done by the teacher in the learning process on the reading activities using Vidio to learn to read, using letters cards and Learning guidance.